Determination the Knowledge, Attitudes and Perceptions of Mothers (Caregiver) Towards Immunization of their Children in South Punjab Region of Pakistan - Syed Razi Abbas, Hamza Qadir, Hafiz Muhammad Naeem Tariq, Samia Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the knowledge, attitudes and perceptions of mothers (caregiver) towards immunization of their children. Methodology: This community based cross-sectional KAP study was conducted in 15 UCs of south Punjab. Multistage random sampling technique, lottery method and bottleneck method was used to select the tehsils, UCs and households for the study. Households with children between eighteen to twenty-four months of age and Mothers/Caregivers with age between twenty to fifty years were included in the study. The semi-structured questionnaire was used to calculate the knowledge and attitude score of the study participants. Data were analyzed in SPSS version 25. Results: Parents/caregivers had good knowledge (50.80%), moderate knowledge (42.40%) and poor knowledge (6.80%)regarding routine immunization. Also, parents/caregivers had a positive attitude (86.40%), neutral attitude (8.70%) and negative attitude (4.90%).The majority of children (67.40%) were fully immunized followed by partially immunized children (25.80%) and non-immunized children (6.80%). Conclusion: The study concluded that parents were well aware regarding immunization and its health-related outcomes and showed positive attitude towards immunization. Majority of the children were completely immunized for all the childhood vaccine preventable diseases and the ratio of non-immunized children was very low as compared to completely and partially immunized population have awareness regarding immunization. Keywords: Knowledge, attitude, practice, Southern Punjab, Pakistan, Developing Country